Tinjauan Yuridis Carding Sebagai Kejahatan TransnasionalTerorganisir - haris kusuma wardana haris; Wahyu Hariadi; Teguh Anindito (Wijayakusuma Law Review, 2021)
Carding is a part of cybercrime that appears from the development of information technology which is not onlyhave a positive impact but also the negative impact for the users. The number of carding’s cases proved that thiscrime is a big threat to society both nationally and internationally. This research will discuss whether cardingcan be categorized as a transnational organized crime and how the government’s efforts in undertaking cardingthrough penal and non-penal policy. The methodology used in this law research is a normative juridical research.The specification of the research used in this law research is descriptive analytical. The methodology used incollecting data by the writer is researching the literature or the secondary data, then analyzed it using analyticalqualitative methods. Based on the result of this research can be concluded that neither the Budapest Conventionon Cybercrime nor the Law of the Republic of Indonesia Number 11 of 2008 Concerning Electronic Informationand Transactions did not directly mention the carding as a crime. According to the elements of carding, it can becategorized as a cybercrime which can be done transnationally.